A User Identity Management Protocol for Cloud Computing Paradigm - Eludiora, Safiriyu Ijiyemi; Oluwatope, Ayodeji; Abiona, Olatunde; Oluwaranti, Adeniran (International Journal of Communications, Network and System Sciences, 2023)
volume 4, pages 152-163